Methods for the protection of transmitted information system remote monitoring and control high-tech objects - I. A. Kalmykov; V. P. Pashintsev; O. V. Velts; M. I. Kalmykov (Вестник Северо-Кавказского федерального университета)
There is a view on the methods for protection of the information transferred between a remote object and the centre for support system monitoring, control, and management of critical technologies. The item offers an imito-protection algorithm reducing the likelihood of imposing false data.